Antioxidant Activity And Nephroprotective Effects Of Aqueous Extract Of Pleurotus Eous (Berk.) Sacc.: (APK1) Pink Edible Oyster Mushroom - VADIVUKKARASI SASIKUMAR; SUDHA. G. MENON (International Journal of Pharma and Bio Sciences, 2011)
Pleurotus eous is an edible oyster mushroom currently available in Southern part of India. There is no information about the antioxidant and therapeutic properties of this mushroom. Pleurotus eous aqueous extract (PEAE) were prepared and analysed for their antioxidant activity by in vitro assays such as DPPH, hydroxyl radicals, Ferric Thiocyanate (FTC) and Thiobarbituric acid (TBA) test. The nephroprotective effect was determined by cisplatin administration which induces a marked renal failure in swiss albino mice and on extract treatment at 500 and 1000 mg/kg body weight, the destroyed renal cells were regenerated. The present study reveals the medicinal beneficial effects of this mushroom which have not been explored so far. The active components responsible for these activities have to be determined.